HOW ORGANIZATIONAL FOUNDATIONS SHAPE CHINESE AI INNOVATION PERFORMANCE - Yu Zhao; Paitoon Pimdee; Aukkapong Sukkamart (Veredas do Direito Direito Ambiental e Desenvolvimento Sustentável, 2026)
Chinese AI firms do not just need to spend on technology. They also need to turn organizational resources into real innovation ability. We tested a model linking organizational learning (OL), knowledge management (KM), human capital (HC), and social capital (SC) to innovation capability (IC) and innovation performance (IP). Using survey data from 362 managers across China's three main AI clusters, we found that OL, KM, and HC boost IC — but SC does not. For IP, OL, HC, SC, and IC all help, while KM does not directly matter. The mediation story is nuanced: OL and HC work both directly and indirectly through IC; KM works only indirectly; SC works directly, bypassing IC entirely. Our findings suggest that in China's AI industry, innovation capability is a selective bridge, not a universal one.
Keywords: Innovation and Knowledge Management; Intellectual Capital and Performance Analysis; Knowledge Management and Sharing